An Analysis of the Concepts of Merit and Sin and Their Implications for the Work Ethic of Madrasah Diniyah Teachers: Analisis Konsep Pahala dan Dosa serta Implikasinya terhadap Etos Kerja Guru Madrasah Diniyah - Muaz, Muaz; Amin, Arip (CV. Media Publikasi Profesional, 2025)
This article aims to discuss the concepts of merit (reward) and sin in Islamic teachings and their implications for the work ethic of teachers at Madrasah Diniyah Al-Faruq Majalengka. In Islam, merit and sin are integral components of the ethical doctrine that influence individual behavior. A sound understanding of these concepts plays a vital role in shaping work motivation. Actions considered virtuous according to Islamic teachings are rewarded (merit), while violations of religious principles result in sin. Using data collection methods such as surveys, observation, interviews, and questionnaires, this study found a significant relationship between teachers’ understanding of the concepts of merit and sin and their level of work ethic. The greater the understanding of these concepts, the better the work ethic demonstrated in daily activities. This suggests that theological understanding can serve as an internal motivator in enhancing work quality, discipline, and professional responsibility among teachers. The main contribution of this article is to show that theological aspects, particularly the understanding of merit and sin can be important variables in shaping work ethic. This study offers a new perspective that improving teachers’ work ethic can be pursued not only through technical training but also by strengthening internal spiritual and religious values.